Assertive Speech Acts in Ryan Adriandhy's Film Jumbo and Its Relevance as an Indonesian Language Teaching Module in High Schools - Lidia Kristiani Situmorang; Erwin Salpa Riansi; Agus Iryana (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Assertive speech acts are a form of speech act used by speakers to convey information, opinions, or beliefs that are considered true. This study examines the form and function of assertive speech acts in the film Jumbo by Ryan Adriandhy and its relevance as an Indonesian language teaching module in high school. The study used a qualitative method with data sources in the form of dialogues between characters in the film Jumbo. Data were collected through listening methods with tapping techniques, free conversational engagement techniques, and note-taking techniques, then analyzed using the pragmatic equivalent method by considering the context of the speech through the SPEAKING model. The results of the study showed that there were 55 assertive speech act data consisting of 27 news sentences, 15 interrogative sentences, and 13 imperative sentences. The functions of assertive speech acts found included stating (11 data), informing (10 data), suggesting (10 data), boasting (5 data), complaining (6 data), demanding (7 data), and reporting (6 data). The research findings show that assertive speech acts in the film Jumbo have a variety of forms and functions and are relevant to be used as material for compiling Indonesian language teaching modules for grade XI SMA on the material of writing short stories.